Strength training in explosive-type sports: Athletics - jumping - Nielsen, L. (Anvendt styrketræning, Styrketræning for sprint og spring 2, Symposie ved Institut for Idræt og Biomekanik, Syddansk Universitet, 2006)
This presentation will focus on the physical training and special on the strength training in the women Long Jump, and I will try to describe my philosophy in my work and go a little more in to details about the main points that I have the most focus on during my planned strength training.